1 Supporting family carers in best interest decision-making in dementia care at the end of life: findings from a cluster randomised control trial. Issue 3 (1st September 2017) - Brazil, Kevin; Carter, Gillian; Cardwell, Chris; Clarke, Mike; Hudson, Peter; Froggatt, Katherine; McLaughlin, Dorry; Passmore, Peter; Kernohan, W George
Abstract : Background: Dementia is a leading cause of death worldwide. Often, people with moderate to advanced dementia are admitted to nursing homes for specialist care. When a person with dementia no longer has the capacity to make decisions about their care, nursing home staff, in combination with family members, may have to make decisions based on a person's best interests. Family carers often report feeling unprepared to participate in these decisions. Advance Care Planning (ACP) can support family carers in best interest decision-making on goals of care at the end of life. However, given its relative importance, the prevalence of ACP in dementia care is poor. This study set out to examine the effectiveness of an intervention designed to facilitate ACP with family carers. Methods: A paired cluster randomised controlled trial was employed. The intervention comprised: a trained facilitator; family education; family meetings; documentation of ACP decisions; and intervention orientation for GPs and nursing home staff. Twenty-four nursing homes with a dementia nursing category located in Northern Ireland, UK participated. Family carers of nursing home residents classified as having dementia and judged as not having decisional capacity to participate in ACP discussions were invited to take part. Participants completed postal questionnaires prior to receiving the intervention or usual care and again, six weeks later. Results: 12 nursing homes were allocated to each group, 11 from intervention and 12 from usual care were analysed. The primary outcome was family carer uncertainty in decision-making about the care of the resident as measured by the Decisional Conflict Scale (DCS). There was evidence of a reduction in total DCS score in the intervention group compared with the usual care group (−10.5, 95% confidence interval −16.4 to −4.7; p<0.001). Conclusions: The ACP was effective in reducing family carer uncertainty in decision-making concerning the care of their family member and improving perceptions of quality of care in nursing homes. Implications for clinicians and policy makers include the need to recognise the importance of family carer education and improving communication between family carers and formal care providers.